Participation of TRPV1 in the activity of the GnRH system in male rats - Surkin, Pablo Nicolas (2020)
GnRH neuron activity is under the influence of multiple stimuli, including those coming from the endocannabinoid and the immune systems. Since it has been previously suggested that some of the main elements controlling the GnRH pulse generator possess the TRPV1 receptor, the aim of the present study was to evaluate the participation of the hypothalamic TRPV1, through its pharmacological blockade, in the activity of the hypothalamic-pituitary-testicular axis in male rats under basal or acute inflammatory conditions. Our hypothesis was based on the idea that the hypothalamic TRPV1 participates in the synthesis of the main neuromodulatory signals controlling GnRH, and therefore the reproductive axis. Our results showed that the hypothalamic TRPV1 blockade induced pro-inflammatory effects by increasing Tnfα and Il-1β mRNA Hypothalamic levels, and inhibited the reproductive axis by affecting Gnrh, Kiss1 and Rfrp3 mRNA levels and decreasing plasma levels of luteinizing hormone and testosterone under basal conditions, without significant additive effects in rats exposed to systemic LPS. Altogether, these results suggest that the hypothalamic TRPV1 receptor participates in the regulation of the GnRH system, probably by modulating immune-dependent mechanisms.